2008
DOI: 10.1128/jb.01008-08
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Galactose Enzymes in Escherichia coli Is Independent of the C-1-Hydroxyl Optical Configuration of the Inducer d -Galactose

Abstract: The two optical forms of aldohexose galactose differing at the C-1 position, ␣-D-galactose and ␤-D-galactose, are widespread in nature. The two anomers also occur in di-and polysaccharides, as well as in glycoconjugates. The anomeric form of D-galactose, when present in complex carbohydrates, e.g., cell wall, glycoproteins, and glycolipids, is specific. Their interconversion occurs as monomers and is effected by the enzyme mutarotase (aldose-1-epimerase). Mutarotase and other D-galactose-metabolizing enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…We therefore conclude that b-anomer of galactose is capable of inducing the GAL/LAC regulon. A similar conclusion was also drawn in the E. coli gal operon by Lee et al (2008), although the molecular mechanism for the galactose induction is fundamentally different in these organisms.…”
Section: Successful Induction Of B-galactosidase By B-anomer In the Cellsupporting
confidence: 71%
See 1 more Smart Citation
“…We therefore conclude that b-anomer of galactose is capable of inducing the GAL/LAC regulon. A similar conclusion was also drawn in the E. coli gal operon by Lee et al (2008), although the molecular mechanism for the galactose induction is fundamentally different in these organisms.…”
Section: Successful Induction Of B-galactosidase By B-anomer In the Cellsupporting
confidence: 71%
“…A similar conclusion was also drawn in the E. coli gal operon by Lee et al . (), although the molecular mechanism for the galactose induction is fundamentally different in these organisms.…”
Section: Resultsmentioning
confidence: 97%
“…After the cells were grown to OD600 of 0.5 in M63 minimal medium containing 0.3% D-fructose and 0.1% casamino acids, 0.3% D-galactose was added and cells were further grown for 1.5 h. The activity of ␤-galactosidase synthesis in cells was measured as described previously (30). Gus assay of galP1 and -P2 was carried out as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…Does accumulation of UDP-galactose or any other intermediate cause induction of gal transcription in the galE Ϫ mutant cells? In vitro transcription assays showed that only D-galactose and not any of the metabolic intermediates, galactose-1-phosphate, UDPgalactose, or UDP-glucose, acts as an inducer of P1 or P2 transcription (20). Thus the accumulated UDP-galactose is unlikely to modulate gal transcription directly in vivo.…”
Section: Consequences Of Utpmentioning
confidence: 97%
See 1 more Smart Citation